O Conceito de Existência em Ser e Tempo - SILVA, Eliana Borges da (2010)
This work discusses the concept of existence, presented in major work of Martin Heidegger, Being and time. This concept will be characterized as the singular way of being of the man, named in the context of Being and time, Dasein. Thus, we address the issue in four stages. At first, we present a brief exposition of Heidegger s ontological project, necessary for a correct understanding of all this work. At this time, should be highlighted why Dasein figure as the privileged being and, thus, thematized throughout the book. In the second phase, the theme being developed is the existence as a new way of understanding the entity that exists always in relation with being. Since, in Being and time, Heidegger abandons the older categories that only apply to entities other than ourselves, and forge the existential expression to refer to the characteristics of Dasein. In the third step we will address the opening of existence as the place where the manifestation of being is given, as will e shown that the decay is the instance that characterizes the improper existence, but through the anguish it can choose to be at their own since it do not run away to be faced with their true condition. Finally, at the last moment of our thesis, the aim is to explain how the phenomenon of death and conscience allow the fundamental openness of Dasein to its own existence.